MARKETING STRATEGY ASSISTANCE AS OPTIMIZATION OF THE EXISTENCE OF MANDIRI SEJAHTERA COMAL BUMDES - Fitri Yulianti; Dina Fauziyah Mufidah; Meta Febrianti; Hendri Hermawan Adinugraha (Journal of Islamic Economy and Community Engagement, 2021)
The purpose of this service activity is to improve business development and assistance to strengthen product marketing strategies in the Sidorejo Village-Owned Enterprises (BUMDes). This service activity is focused on developing BUMDes businesses and implementing marketing methods for BUMDes Desa Sidorejo Comal both with conventional methods and via the internet. The service methods used are: (1) Conducting initial observations and interviews with BUMDes management and community leaders. and (2) the stages of implementing the activities. The result achieved is that the management of the Sidorejo Village BUMDes can improve marketing strategies both through conventional and the internet as an optimization of the existence of Sidorejo Village BUMDes.